Evaluación de características bromatológicas y microbiológicas en un yogur usando tres variedades de zapallo como ingrediente alternativo en la industria láctea - López Mendoza, Gema Dolores (2021)
Bromatological and microbiological characteristics were evaluated in a yogurt-type fermented milk, made with three varieties of squash, added in the form of jelly: Cucurbita maximum, Cucurbita pepo and Cucurbita moschata, as an alternative ingredient; using two relationships per variety, 15% and 30%. The research was adjusted to a Completely Random Design (DCA) with a bifactorial AxB arrangement of six treatments with three replications of each one. The results were analyzed in the statistical program IBM SPSS version 21, where it was shown that the jelly of the variety Cucurbita moschata in relation of 30% corresponding to T6, presented better bromatological characteristics of: acidity (0.94%), pH (4 , 08) and protein (3.91%) in relation to the other varieties of jellies, in accordance with the provisions of the NTE INEN 2395 (2011) standard. The treatments were evaluated microbiologically, where it was shown that all these were within the parameters established by the NTE INEN 2395 standard, being subjected to an affective sensory test by preferences, data that was analyzed using Friedman's non-parametric statistical test, showing that T4 made with 30% Cucurbita pepo jelly was the most preferred among the treatments.